Pathos versus Ideal in Classical Greek Sculpture and the Parian Output - Katsonopoulou, Dora (Actual Problems of Theory and History of Art, 2015)
The fourth century BC although coupled together with the fifth century under the term Classical, is both historically and artistically a different era. Especially in art, particularly the sculpture, new traits are seen already in the early years of the century tending to divert from the Classical harmonious forms and ideal faces of the 5th century. Intensity and vital feelings become now the main tendency expressed in body forms and faces of sculptured figures. This tendency, generally considered as first seen ca 380 BC in the Epidauros sculptures, becomes dominant around the middle of the century when the new style of expressing pathos is well established. The evident departure of the art in the 4th century BC from the Classical ideal and its turn to the expression of strong emotions seem to reflect new prevailing attitudes in the political and social life of the Greeks. The sculptor who is mainly associated with the new style and became its real master, is Skopas from the island of Paros, active between 370–330 BC, a close contemporary of Praxiteles of Athens. In the paper it is argued that Skopas’ prolific career and distinctive art began in Paros, where the origins of his style are to be found. To this end, certain sculptures from Paros preceding Skopas’ age are discussed suggesting that the beginnings of the new trend in sculpture of the 4th century BC should be rather placed in Paros of the early 5th century BC than in Epidauros of the 4th century as considered until today.